Family presence during resuscitation in a paediatric hospital: health professionals’ confidence and perceptions - McLean, Julie A. (Curtin University, 2013)
Embracing the philosophy of family-centred care, family presence during resuscitation remains a controversial practice amongst healthcare professionals. A descriptive cross-sectional questionnaire study design investigated medical and nursing staff perceptions of and self-confidence in facilitating family presence during resuscitation in a children’s hospital. All staff held positive perceptions and staff in critical care areas with experience in resuscitation and family presence, perceived more risk/benefits and more self-confidence than staff in non-critical care areas without resuscitation experience.